Chapter twenty‐five kinetoplastida: Model organisms for simple autophagic pathways? - Denninger, V.; Koopmann, R.; Muhammad, K.; Barth, T.; Bassarak, B.; Schonfeld, C.; Kilunga, B.K.; Duszenko, M. (Elsevier, 2008)
Phylogenetic analyses based on defined proteins or different RNA species have revealed that the order kinetoplastida belongs to the early‐branching eukaryotes and may thus contain organisms in which complex cellular events are easier to analyze. This view was further supported by results from a bioinformatic survey that suggested that nearly half of the autophagy‐related proteins existent in yeast are missing in trypanosomatids. On the other hand, these organisms have evolved a highly sophisticated machinery to escape from the different host immune‐response strategies and have learned to cope with extremely variable environmental conditions by morphological and functional reorganization of the cell. For both the stress response and the differentiation processes, autophagy seems to be an indispensable prerequisite. So far autophagy has not been systematically investigated in trypanosomatids. Here we present technical information on how to handle the different parasites belonging to this order and give an overview of the current status of autophagy research in these organisms.